(untitled) (UNWE Yearbook, 2023)
The paper examines certain aspects of the methodology of Foreign Language Teaching (FLT), final examinations, scientific research, some publications and international activities, provided by one of the largest and oldest departments of the UNWE. Traditionally perceived in our academic community as providing basically practical training in English, Spanish, Russian, German and French, as well as Bulgarian language for foreigners, our foreign language department has made serious progress in the research field. Furthermore there has been a significant increase in the publications in the area of academic books and scientific research, despite the drastic downsizing of its academic faculty of lecturers. Different periods of FLT have been interpreted and examined. The article is dedicated to the centenarian anniversary of the University of National and World Economy, the biggest higher school of economics and business in South-eastern Europe.